Performance and the global city (Palgrave Macmillan, 2013)
"Following the ground-breaking Performance and the City, this new volume explores what it means to create and experience urban performance - as both an aesthetic and a political practice - in the burgeoning world cities built by globalization and neoliberal capital. Featuring work by artists as well as scholars, written from multiple disciplinary perspectives, and including dozens of photographs as well as a photo essay by Nicholas Whybrow, Performance and the Global City will appeal to readers interested in urban studies, theatre and performance, geography, sociology, and globalization studies"--